TAXONOMY AND GENETIC RELATIONSHIPS OF PANGASIIDAE, ASIAN CATFISHES, BASED ON MORPHOLOGICAL AND MOLECULAR ANALYSES - Rudhy Gustiano; Laurent Pouyaud (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2007)
Pangasiids are economically important riverine catfishes generally residing in freshwater from the Indian subcontinent to the Indonesian Archipelago. The systematics of this family are still poorly known. Consequently, lack of such basic information impedes the understanding of the biology of the Pangasiids and the study of their aquaculture potential as well as improvement of seed production and growth performance. The objectives of the present study are to clarify phylogeny of this family based on a biometric analysis and molecular evidence using 12S ribosomal mtDNA on the total of 1070 specimens. The study revealed that 28 species are recognised as valid in Pangasiidae. Four genera are also recognized as Helicophagus Bleeker 1858, Pangasianodon Chevey 1930, Pteropangasius Fowler 1937, and Pangasius Valenciennes 1840 instead of two as reported by previous workers. The phylogenetic analysis demonstrated the recognised genera, and genetic relationships among taxa. Overall, trees from the different analyses show similar topologies and confirm the hypothesis derived from geological history, palaeontology, and similar models in other taxa of fishes from the same area. The oldest genus may already have existed when the Asian mainland was still connected to the islands in the southern part about 20 million years ago.